2011
DOI: 10.1111/j.1365-2486.2011.02589.x
|View full text |Cite
|
Sign up to set email alerts
|

On the forest cover–water yield debate: from demand‐ to supply‐side thinking

Abstract: Several major articles from the past decade and beyond conclude the impact of reforestation or afforestation on water yield is negative: additional forest cover will reduce and removing forests will raise downstream water availability. A second group of authors argue the opposite: planting additional forests should raise downstream water availability and intensify the hydrologic cycle. Obtaining supporting evidence for this second group of authors has been more difficult due to the larger scales at which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
340
1
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(368 citation statements)
references
References 70 publications
(139 reference statements)
15
340
1
12
Order By: Relevance
“…Table 4), possibly due to biases in the PRISM P map, uncertainties in the Q and/or catchment boundary data, water extractions, inter-basin groundwater transfers (potentially exacerbated by karst), and/or water recycling (e.g. Ellison et al, 2012), which combined may cancel out or amplify The decrease in Q was explained by the higher ET a of the regenerating vegetation. e Refers to changes in peak flows only.…”
Section: Hbv-light Model Performancementioning
confidence: 99%
“…Table 4), possibly due to biases in the PRISM P map, uncertainties in the Q and/or catchment boundary data, water extractions, inter-basin groundwater transfers (potentially exacerbated by karst), and/or water recycling (e.g. Ellison et al, 2012), which combined may cancel out or amplify The decrease in Q was explained by the higher ET a of the regenerating vegetation. e Refers to changes in peak flows only.…”
Section: Hbv-light Model Performancementioning
confidence: 99%
“…Previous studies that estimated the amount of water resources or the supply service of the Korean forestry [3,52,53] focused on assessing the current supply of water. On supply-side thinking, afforestation will raise water supply and strengthen the hydrological cycle [54]. Furthermore, vegetation destruction and land cover change resulting from deforestation could be the main cause of soil degradation and soil loss [41,55].…”
Section: Implications Of National Scale Afforestation To Other Regionsmentioning
confidence: 99%
“…Research have shown that forest harvesting has increased streamflow and rates of snowmelt and generally, such condition will occur in small headwater 2 catchments (< 1 km ). This shows that forest's role and its impact on water yield (including hydrologic cycle) varied and is still debated (Andre´assian 2004;Ellison et al 2012). Based on the weakness, this researches use a single catchment approach to evaluate the impacts of forest reduction on river discharge at large scale catchment (i.e.…”
Section: Introductionmentioning
confidence: 99%